A systematic review to study the efficacy of cognitive behavioral therapy for sexually abused children and adolescents with posttraumatic stress disorder (Archives of Clinical Psychiatry, 2010)
BACKGROUND: Posttraumatic stress disorder (PTSD), one of the possible consequences of sexual abuse of children and adolescents, may be found in about 40% to 50% of the cases. OBJECTIVES: Conduct a systematic review of studies investigating the use of cognitive behavioral therapy (CBT) for the treatment of sexually abused children and adolescents with PTSD. METHODS: A search for randomized clinical trials that evaluated PTSD in children and adolescents from 1980 to February 1, 2006 was conducted in the following databases: MedLine, EMBASE, LILACS, PsycLIT, PsycINFO, Cochrane Depression, Anxiety and Neurosis Group Database of Trials, Cochrane Controlled Trials Register, Science Citation Index (SciSearch), and PILOTS. References in all clinical trials selected were hand-searched. RESULTS: Of the 43 studies initially selected, only three met inclusion criteria. The following comparisons were found in the studies: CBT to treat child and family member versus no treatment (waiting list); CBT to treat only child, only parents, or both versus community care; and trauma-focused CBT versus child-centered therapy (CCT). Results for CBT treatment of PTSD were better than no treatment (waiting list) (p < 0.05), community care (p < 0.01) and CCT (p < 0.01). The comparison of child-only CBT and family CBT (parents or caretakers and children) did not reveal any significant differences in efficacy, and both showed significant improvement of symptoms. A meta-analysis was conducted to compare the efficacy of CBT (child-only and family) versus no treatment (waiting list and community care) in the remission of patients who completed treatment. Remission rates in treatment and control groups were 60% and 20%, and this difference in favor of CBT was statistically significant (RR = 0.51; 95%CI 0.29-0.88; p = 0.02). No controlled studies were found that compared CBT and pharmacotherapy. DISCUSSION: Treatment with CBT reduces PTSD symptoms in sexually abused children and adolescents, with no differences between therapy with only the victim or with the victim and a family member. No studies compared CBT and pharmacotherapy or the efficacy of combined treatments.